Master your next move : the essential companion to The first 90 days - Watkins, Michael, 1956- (Boston, Massachusetts : Harvard Business Press, 2019)
Your next professional move can make or break your career--are you ready? In business, especially today, you are only as successful as your next career transition. Do well, and you'll be on the fast track to even more challenging roles. Fail, and you could irreparably harm your career--and your organization. In his international bestseller The First 90 Days, transition guru Michael D. Watkins outlined a set of common principles for getting up to speed quickly in new professional roles. Since that book was published, Watkins has worked with thousands of leaders helping them to accelerate their transitions. These leaders posed challenging questions on how to apply the basic principles in real-life situations. The truth that emerged: The First 90 Days framework can be applied in every transition, but the way you apply it is entirely different when you have been promoted to a higher level than it is when you are joining a new organization, or taking a role in a different country. Master Your Next Move answers this distinct need, focusing on the most common types of transitions leaders face and the unique challenges posed by each. Based on years of research, and now with a new introduction, this indispensable book explores eight crucial transitions virtually everyone faces during their career, including promotion, leading former peers, onboarding into a new company, making an international move, and turning around a business in crisis. With real-world examples and lots of practical models and tools, Master Your Next Move is your guide to surviving and thriving as you make your next move...and every one after that.--
Introduction: Mastering your next move -- Successful careers as a series of challenging transitions into new roles: mapping the critical categories of career moves, meeting the personal adaptive challenge and the organizational change challenge -- The promotion challenge: understanding what "success" looks like a higher level in the hierarchy, adjusting your focus and approach to delegation, developing new leadership competencies and cultivating "presence" -- The leading-former-peers challenge: being promoted to manage people who were formerly your peers, deftly establishing your authority in the new role, re-engineering existing relationships, dealing with problematic former peers -- The corporate diplomacy challenge: moving from a position of authority to one in which strong influence skills are critical for getting things done, mapping the influence landscape, building supportive alliances -- The on-boarding challenge: joining a new organization and adapting to new culture, the pillars of effective on-boarding, building the right political "wiring", aligning expectations up, down, and sideways -- The international move challenge: moving to a new country and leading people in an unfamiliar culture, moving one's family and rebuilding the support system, preparing for entry, beginning to engage with the team and the business -- The turnaround challenge: taking over an organization that is in very deep trouble and figuring out how to save it from destruction, diagnosing the situation, designing the business model, driving alignment and dynamically adapting -- The realignment challenge: confronting an organization that is in denial about the need for change, creating a sense of urgency, before emerging problems erupt in a crisis, adjusting your leadership style to match the situation -- The STARS portfolio challenge: leading an organization in which different parts are in different states -- startup, turnaround, accelerated growth, realignment, and sustaining succe
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on December 14, 2020).
Master record variable field(s) change: 050
Keywords: Career development; Success in business; Leadership; Strategic planning; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Reference; BUSINESS & ECONOMICS / Skills; Career development; Leadership; Strategic planning; Success in business; elektronické knihy; electronic books